A laboratory exercise to improve student understanding of dominant pole analysis and high-frequency modeling of Field Effect Transistors. Issue 2 (April 2015) - Kim, Ernest M; Schubert, Thomas F
In the quest for increased student understanding of the principles underlying high-frequency response of Field Effect Transistor amplifiers, a laboratory exercise employing a unique method to determine the intrinsic transistor model capacitances was used. The method employs two simple measurements: determination of the high 3-dB frequency for a common-source amplifier being driven by a Thévenin source with two different output resistance values. Circuit simulation results utilizing these experimentally determined intrinsic capacitances show much greater correlation to experimental results than those typically obtained using manufacturer-supplied values. Students participating in the laboratory exercise reported good gains in knowledge levels and reasonable gains in confidence levels.